W‐Band MMIC chipset in 0.1‐μm mHEMT technology. Issue 4 (14th August 2020) - Lee, Jong‐Min; Chang, Woo‐Jin; Kang, Dong Min; Min, Byoung‐Gue; Yoon, Hyung Sup; Chang, Sung‐Jae; Jung, Hyun‐Wook; Kim, Wansik; Jung, Jooyong; Kim, Jongpil; Seo, Mihui; Kim, Sosu
Abstract : We developed a 0.1‐μm metamorphic high electron mobility transistor and fabricated a W‐band monolithic microwave integrated circuit chipset with our in‐house technology to verify the performance and usability of the developed technology. The DC characteristics were a drain current density of 747 mA/mm and a maximum transconductance of 1.354 S/mm; the RF characteristics were a cutoff frequency of 210 GHz and a maximum oscillation frequency of 252 GHz. A frequency multiplier was developed to increase the frequency of the input signal. The fabricated multiplier showed high output values (more than 0 dBm) in the 94 GHz–108 GHz band and achieved excellent spurious suppression. A low‐noise amplifier (LNA) with a four‐stage single‐ended architecture using a common‐source stage was also developed. This LNA achieved a gain of 20 dB in a band between 83 GHz and 110 GHz and a noise figure lower than 3.8 dB with a frequency of 94 GHz. A W‐band image‐rejection mixer (IRM) with an external off‐chip coupler was also designed. The IRM provided a conversion gain of 13 dB–17 dB for RF frequencies of 80 GHz–110 GHz and image‐rejection ratios of 17 dB–19 dB for RF frequencies of 93 GHz–100 GHz.